O discurso escolar: uma análise sobre o olhar do aluno - Sabeh, Mirian Valéria Gomes [UNESP] (2015)
The study in question has the intention to analyze the meaning of the conception of this school in the discourse of primary school students, specifically the 7th school year. To reflect on their meanings, first of all, it is necessary to give a voice to students. The aim is to analyze whether and how power relations emerge in the speeches of students in a space where there are conflicts and dialogues influenced by hierarchical power games and authoritarian teaching methods. Based on the analysis of the French Discourse, especially in studies of the microphysics of power Foucault and studies of language of Bakhtin Circle, we intend to think the relationship between macro and micro-powers, given the institutionalized hierarchy (including as State symbol, according to Althusser) and the peripheral, considered marginal. To foster discussions required, will be adopted the song clip Another brick in the wall, the Pink Floyd band, the motto and significant contribution to identifying relationships between the institution and the student community, as well as how power relations penetrate and influence the teaching-learning in teacher and student relationships, student and school, institutionalized knowledge and social experiences